МОНГОЛ УЛСЫН ИХ ХУРЛЫН ТӨЛӨӨЛЛИЙН ЧИГ ҮҮРГИЙН ХЭРЭГЖИЛТИЙГ ҮНЭЛЭХ НЬ - Ж.ТӨРТОГТОХ; Г.Туяагэрэл (Politology, 2024)
In the theory of democracy, Parliament, is an institution of representation that creates a universally recognized legal entity that expresses national interests. Mongolia has been transitioning to a parliamentary system for 30 years, but the fundamental role of representing the people of the legislative constitution and strengthening representative democracy has been blurred, resulting in a decline in public trust in the institution. Therefore, in this study, we evaluated the representation functions of the Mongolian Great Ikh Khural, established in the 2020 elections, based on the views of researchers on the role of representation, as well as the participation of citizens and voters in the legislative process.